Analisis Maqāṣid al-Syarī‘ah terhadap Penyaluran Program Bantuan Rumah Layak Huni Baznas: Studi Kasus Baznas Kabupaten Nias - Zai, Khaeran Nadyah; Zahara, Fatimah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the implementation of the Livable Housing Assistance Program (RLH), the mechanism of zakat distribution, and its conformity with the perspective of maqāṣid al-sharī‘ah. The problem addressed in this study is that although the RLH program by BAZNAS of Nias Regency serves as an effort to utilize zakat funds to assist low-income communities, there remains a gap between the high demand for livable housing and the limited realization of assistance. This research is motivated by the large number of uninhabitable houses in Nias Regency and the limited collection of zakat funds, which contribute to the disparity between needs and program implementation. This study employs an empirical legal research method with a qualitative approach, using interviews and literature review as data collection techniques. The findings indicate that the RLH program is implemented systematically and in a targeted manner, providing positive impacts on the beneficiaries’ quality of life. From the perspective of maqāṣid al-sharī‘ah, the program fulfills the aspects of protection of religion, life, intellect, lineage, and wealth, thus functioning not only as a consumptive aid but also as an empowerment instrument in achieving sustainable social welfare.